Analysis of Fresh Cuttlefish Handling Practices and Their Relationship with Product Quality at PT Buana Ikan Nusantara Industri - Kurnia Bislana Afdal; Juhardin Juhardin; Anwar Said (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
Research on the handling of fishery products generally focuses on laboratory-based quality testing, while studies examining handling practices directly within industrial settings and their conformity with standards remain limited. This study aims to analyze the handling practices of fresh cuttlefish at PT Buana Ikan Nusantara Industri and to evaluate their conformity with the Indonesian National Standard (SNI 6926.3:2011) in relation to product quality. The method employed was descriptive observation with an evaluative approach through direct observation and semi-structured interviews conducted during the period of April–July 2025. The analysis was carried out by comparing each stage of the handling process with quality control parameters established in the SNI, including aspects of sanitation, temperature control, freezing, packaging, and storage. The results indicate that most handling stages are in accordance with the SNI provisions, particularly in the processes of washing, arrangement, freezing using Air Blast Freezer (ABF), and frozen storage applying the FIFO system. The observed quality indicators include the sensory condition of raw materials (color, texture, and natural mucus), temperature control, and product stability during storage. However, potential risks were identified in the visually based sorting stage and in the use of chlorine, which requires strict control to prevent residue. These findings demonstrate that conformity with standards and consistency in control at each stage of the process are key factors in maintaining the quality of frozen cuttlefish products. This study contributes an empirical evaluation of the implementation of handling standards in the fish processing industry